Psychometric properties of the revised organizational citizenship behaviour questionnaire - Bagdžiūnienė, Dalia; Lazauskaitė-Zabielskė, Jurgita; Urbanavičiūtė, Ieva (Psichologija, 2019)
Organizational citizenship behaviour is defined as “individual behaviour that is discretionary and not directly or explicitly recognized by the formal reward system and in the aggregate promotes the efficient and effective functioning of the organization” (Organ, Podsakoff, & MacKenzie, 2006). Nowadays it is one of the most widely studied phenomena in the field of organizational science (Podsakoff, Podsakoff, MacKenzie, Maynes, & Spoelma, 2014). Employee citizenship behaviour generates additional value for the organization by creating a positive social environment, improving the use of resources, coordinating activities within and between working groups, enhancing the organization’s ability to attract and retain the best employees, maintaining organizational stability and adaptability to environmental changes. Meanwhile, citizenship behaviour is not widely studied in Lithuania and one of the reasons may be a lack of reliable and valid instruments that would correspond to the country’s cultural context. The first version of the Lithuanian twenty-nine items Organizational Citizenship Behaviour (OCB) questionnaire included dimensions of altruism, courtesy, civic virtue, conscientiousness, and was developed in 2013 (Bagdžiūnienė, Lazauskaitė-Zabielskė ir Urbanavičiūtė, 2013). Later, in 2014–2016, two studies were carried out with the aim to revise and confirm the structure of the OCB questionnaire and to re-evaluate its psychometric properties. In the first study, a total of 1985 employees from one Lithuanian public sector organization were surveyed online. Ninety-two percent of the respondents were female, the average age of respondents was 45.13 (SD = 10.3) years, with an average of 12.34 (SD = 7.74) years of working experience in the organization. Thirteen percent of the respondents were first-level managers. Confirmatory Factor Analysis (CFA) confirmed the five factor structure of the questionnaire; however, nine items with the lowest loadings were removed. The shortened version of the OCB questionnaire consists of five dimensions with four items in each scale. Cronbach’s alphas confirmed the reliability of each scale, the discriminant validity was confirmed by positive correlations between OCB dimensions and inrole behaviour, affective organizational commitment, job satisfaction and negative correlations with the intention to quit. In the second study, 647 employees from different organizations were surveyed online. Seventy-four percent of them were female, the average age of respondents was 30.64 (SD = 10.08) years, with an average of 4.45 (SD = 6.19) years of working experience in the organization. Sixteen percent of the respondents were first-level managers. Thirty-two percent of the respondents were from public and sixty-eight percent from private sector organizations. The five-factor structure was additionally approved by applying CFA in this sample, the invariance of the structure regarding gender, age, and status was also confirmed. Conclusion: The revised OCB questionnaire is a reliable and valid twenty-items multidimensional instrument and is congruent with the classical concept of OCB. It includes five dimensions of employee citizenship behaviour, namely altruism, courtesy, civic virtue, conscientiousness, and initiative. Limitations and practical applications are discussed.